2015
DOI: 10.1016/j.ibiod.2015.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Influence of operating pH on biodegradation performance and fouling propensity in membrane bioreactors for landfill leachate treatment

Abstract: This research has investigated the effects of varying mixed liquor pH (i.e. 5.5, 6.5, 7.5, 8.5) on the landfill leachate biodegradability and fouling behavior in two submerged membrane bioreactors (MBR) for a 150-day period. In the experiments, variations in organic removal and dissolved organic matters (DOM) transformation, microbial community and mixed liquor properties as well as the fouling behavior were monitored and systematically analyzed. The findings indicated that the organic removal in both MBRs was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…However, membrane fouling is considered the main drawback, due to the interaction between the membrane and fouling agents, leading to the membrane's efficiency deterioration [66,67]. Moreover, membrane fouling was found to be most severe at pH 5.5, followed by at pH 8.5, while the fouling at pH 6.5 and 7.5 was quite similar and less severe than that at pH 5.5 and 8.5 [68], identifying MBR technology as an expensive and dangerous technical choice for leachate treatment.…”
Section: Membrane Biological Reactor (Mbr)mentioning
confidence: 99%
“…However, membrane fouling is considered the main drawback, due to the interaction between the membrane and fouling agents, leading to the membrane's efficiency deterioration [66,67]. Moreover, membrane fouling was found to be most severe at pH 5.5, followed by at pH 8.5, while the fouling at pH 6.5 and 7.5 was quite similar and less severe than that at pH 5.5 and 8.5 [68], identifying MBR technology as an expensive and dangerous technical choice for leachate treatment.…”
Section: Membrane Biological Reactor (Mbr)mentioning
confidence: 99%
“…This fact can be mainly due to the higher stress of the biomass in MBR-HS, caused by accumulation of non-biodegradable solids (Hao et al, 2010) and high salinity (40.13 ± 4.65 mS/cm) (Jang et al, 2013) that can lead to bacteria stress. MBRs treating landfill leachates, it can be mentioned that Sanguanpak et al, (2015) reported concentrations lower than the SMP obtained in MBR-LS. In fact, the SMPp concentrations measured in MBR-LS are around twice higher than those reported by these authors.…”
Section: Chemical Characterization and Influence On Mixed Liquor Filtmentioning
confidence: 77%
“…Therefore, these bacteria are able to degrade carbohydrates, increasing the relationship between proteins and carbohydrates concentration. by Sanguanpak et al (2015), the measured eEPS concentrations were lower. It is probably due to the low organic matter concentration available for the microorganisms in MBR-LS and MBR-HS.…”
Section: Chemical Characterization and Influence On Mixed Liquor Filtmentioning
confidence: 84%
“…While there is no clear definition of the exact fouling phenomena occurring during filtration, extracellular polymeric substances (EPS) have been widely reported to play a key role in this regard. More specifically, several studies have shown that the biomass supernatant ''Soluble Microbial Product'' (SMP) and its carbohydrate fraction are the main determinants affecting fouling (Sanguanpak et al 2015c;Rosenberger et al 2005;Dvořák et al 2011;Chang et al 2002). The complex interaction of hydrodynamics, mass transfer, biological degradation, and existing compounds makes it difficult to isolate all the parameters that could help in predicting membrane fouling , although the most Defrance and Jaffrin 1999;Vyas et al 2002), the filtration time (short-term vs. long-term; Yang et al 2006;Zhang et al 2006), the operating conditions and cleaning procedures (Sanguanpak et al 2015a;Trussell et al 2006;Cui et al 2003), the setup configuration (external vs. submerged; Xue et al 2015) and the initial stage of the membrane (new vs. cleaned; Le Clech et al 2003).…”
Section: Mbr Limitationsmentioning
confidence: 99%